NILAI DALAM KISAH ALQUR’AN - M. Yarni; Muhammad Ridha (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
One of God's ways in educating humans is by using the story method in the Qur'an. With that method, humans can take the moral message in it, without feeling indoctrinated. Even the educational messages contained therein will be easier to digest and interesting. The main purpose of the narrative of the Qur'an is as a lesson for humans, related to its two functions, namely having to worship God and as khalîfah who must prosper the earth. By using a descriptive-analytic method and a thematic interpretation approach, this article describes the various educational values in the Qur'anic story. monotheism, intellectual, moral, sexual, spiritual, and also democracy.